Service Quality And Brand Awareness Intervention In Affecting Customer Satisfaction At The Bri Bank Pomalaa Unit - Andry Stepahnie Titing; Sudarnice Sudarnice; Almansyah Rundu Wonua (Universitas Mercu Buana, 2022)
This study aims to determine the effect of service quality and Brand Awareness toward customer satisfaction of Bank BRI Unit Pomalaa. The type of research used is Explanatory Research with a quantitative approach. The population in this study are the customers of Bank BRI Unit Pomalaa. The data collected using a questionnaire with samples taken as many as 74 respondent. In analyzing the data in this study using SmartPLS. The result of the partial analysis showed that service quality and Brand Awareness has a positive and significant influence on customer satisfaction. Variables of service quality and Brand Awareness has a positive and significant on customer satisfaction of 82,1%